2013
DOI: 10.1253/circj.cj-13-0305
|View full text |Cite
|
Sign up to set email alerts
|

GABA<sub>B</sub> Receptor Gene Transfer Into the Nucleus Tractus Solitarii Induces Chronic Blood Pressure Elevation in Normotensive Rats

Abstract: Background Increasing evidence indicates that GABAergic neurons in the nucleus of the solitary tract (NTS) play a significant role in the arterial baroreceptor reflex and in the control of cardiovascular homeostasis. However, the role of these neurons in the development of hypertension is not yet fully clear. Methods and Results In the present study, we first confirmed that GABA B receptor (GBR) expression is enhanced in the NTS of SHR as compared with WKY rats using real time RT-PCR and Western Blots. To st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…43 Involvement of the nucleus of the solitary tract (NTS) in the development of hypertension is also reported. 44 In contrast, a mechanism for the shift of the neural arc towards higher input pressure in SHR is less clear. A reduced distensibility of the arterial wall at the baroreceptor regions can change the pressure-diameter relation towards higher input pressure.…”
Section: Discussionmentioning
confidence: 99%
“…43 Involvement of the nucleus of the solitary tract (NTS) in the development of hypertension is also reported. 44 In contrast, a mechanism for the shift of the neural arc towards higher input pressure in SHR is less clear. A reduced distensibility of the arterial wall at the baroreceptor regions can change the pressure-diameter relation towards higher input pressure.…”
Section: Discussionmentioning
confidence: 99%
“…This sympathetic overactivation may be the result of placental pathogenic factors (e.g., inflammatory cytokines) acting primarily on brainstem nuclei that govern sympathovagal balance (154156) of cardiovascular physiology. In other forms of hypertension, the mechanism is disinhibition of the RVLM by upregulating the expression of GABA B receptors in the regions of the nucleus of the solitary tract that receive baroreceptor afferents (Figure 2) (157163). Whether this mechanism is active in PE is an area ripe for new research.…”
Section: The Autonomic Regulation Of Cardiovascular Physiological Adamentioning
confidence: 99%
“…Pharmacologic studies in spontaneously hypertensive rats (SHRs) (162, 208210), and hypertensive Sprague-Dawley rats induced with a one-kidney figure-8 renal wrap (163, 195, 198, 201, 211) have demonstrated that the enhanced expression and activation of GABA B Rs in the regions of the NTS that receive and integrate BR afferent inputs results in hypertension. Additionally, transfer of the GABA B R gene into the NTS of normotensive rats resulted in rapid onset of hypertension, increased heart rate, and increased plasma norepinephrine levels, all of which remained elevated for the duration of the 14-day study (157). This GABA B R-mediated pressor response is potentiated by the actions of AngII on NTS neurons (161).…”
Section: Diverse Models Of Hypertension Demonstrate Electrophysiologimentioning
confidence: 99%
“…Through its role in interpreting interoceptive inputs from the entire body and translating that into autonomic function via the parasympathetic and sympathetic outflows, it forms an attractive target for manipulation. Past studies have shown that manipulations affecting the NTS alone are sufficient to ameliorate hypertension in the SHR model 3,[30][31][32][33] . Many of the pharmacological interventions that show clinical efficacy in lowering blood pressure in hypertensive patients work at many different sites of action in parallel, even if the presumed mechanism of action is narrowly defined.…”
Section: Discussionmentioning
confidence: 99%